The direct and interactive effects of store‐level promotions on impulse purchase: Moderating impact of category familiarity and normative influences. Issue 4 (28th December 2013) - Shukla, Paurav; Banerjee, Madhumita
ABSTRACT Marketing literature conceptually and empirically establishes the direct effects of different variables on impulse purchase. However, the simultaneous interactions between variables influencing impulse purchase are yet to be studied. This paper measures the direct effects of store‐level promotions, brand equity, and price consciousness and also examines the interactive effects of store‐level promotions and the moderating influence of category familiarity and normative influences. The results demonstrate the importance of simultaneous examination of interplay between different consumer and store‐level variables. Collectively, the results provide substantial segmentation opportunities for manufacturers of branded goods and retailers. Copyright © 2013 John Wiley & Sons, Ltd.